Corporate Sustainability Paradox Management: A Systematic Review and Future Agenda - Luo, Ben Nanfeng; Tang, Ying; Chen, Erica Wen; Li, Shiqi; Luo, Dongying (Frontiers in Psychology, 2020)
Increasing evidence suggests that corporate sustainability is paradoxical in nature, as corporates and managers have to achieve economic, social, and environmental goals, simultaneously. While a paradox perspective has been broadly incorporated into sustainability research for more than a decade, it has resulted in limited improvement in our understanding of corporate sustainability paradox management. In this study, the authors conduct a systematic review of the literature of corporate sustainability paradox management by adopting the Smith–Lewis three-stage model of dynamic equilibrium. The results reveal the following. 1) Both environmental and cognitive factors manifest tensions arising from the sustainability paradox. 2) While both proactive and defensive strategies are adopted to manage the tensions embedded in the corporate sustainability, the proactive strategy is more extensively studied in the current literature. 3) Management strategies of corporate sustainability paradox are characterized as multi-level, multi-stage, and dealing with multiple paradoxes. 4) Proactive strategies enable organizations to enjoy short-term and long-term sustainability benefits. The authors call for further research explicitly addressing the following areas: 1) the paradoxical nature of corporate sustainability management; 2) corporate sustainability paradox management of for-profit organizations; 3) the micro-foundations of corporate sustainability paradox management; 4) defensive strategies and new proactive strategies; and 5) a unified standard of sustainability outcomes. The practical implications of this review are then elaborated. In practice, the results imply that organizations would best manage the corporate sustainability paradox by understanding the paradox and its equilibrium stages. This review and proposed research agenda are expected to deepen interdisciplinary knowledge and set the stage for interested scholars to undertake in their future inquiries.